Revitalization Palm Leaf Craft Business - Amrita, Nyoman Dwka Ayu; Sedana, I Dewa Gede Putra (International Journal of Community Service Learning, 2022)
Palm leaf craft is one of the crafts that has good prospects and is in great demand by tourists because it is made of natural materials and has a very artistic shape. The palm leaf craft business is the economic foundation of the community in Madangan Kelod, Gianyar. However, the prospect of this palm leaf craft business is still not optimal. Based on observations, there are palm leaf craft business groups that really need help to overcome the problems they face. The problems faced by this craft business group are inadequate production equipment, lack of insight into online marketing, lack of knowledge of group management, division of tasks members and recording the administration of financial statements carefully and thoroughly. The purpose of this program is create availability of adequate equipment and partners being able to increase the amount of handicraft production by 30%, partners being able to increase sales by 30%, and all members of the craftsman group being able to understand group management and be able to make group bookkeeping. The method of implementing this activity is preceded by collecting information from partners' conditions, designing activities to be carried out, followed by program socialization, conducting training, mentoring and evaluation.